Catalogue of Indonesian Manuscripts Collection Staatsbibliothek Zu Berlin-Preubischer Kulturbesitz-: Bali-Java-Kalimantan-Lombok-Madura-Sulawesi-Sumatra-Sumbawa - Catalogue... (Museum Nasional Indonesia, 2016)
yna, c.1/ yna, c.1